Peran teknologi dalam penerjemahan sastra Arab - Sari, Dewi Masitoh Arum (Maliki Interdisciplinary Journal, 2024)
With globalization, the need for translation of Arab literature is growing. Arab literary translators are faced with complex works full of unique language and cultural nuances. Technology has improved the quality of translation significantly to address this problem. The purpose of this research is to expose about the three technological components important for translation of Arabic literature. The method used in this study is to gather and analyze various relevant literary sources. The results of the research show that some important technological components for Arabic literary translation are automatic translation, specialized translation software, and online translation resources. The technology has contributed significantly to improving the quality of translation of Arab literature. Arab literary translations can higher quality standards with synergies between human translator knowledge and technology.